aO2, SaO2, dan Rasio PaO2/FiO2 Sebagai Prediktor Derajat Keparahan Pasien COVID-19 Rawat Inap - Ngakan Putu Parsama Putra; Aditya Sri Listyoko; Anthony Christanto (PENGURUS BESAR IKATAN DOKTER INDONESIA (PB IDI), 2020)
Introduction: Currently COVID-19 continues to show an increase in prevalence and mortality. Fever, dry cough, fatique and progression to dyspnea even respiratory failure and ARDS are the symptoms of COVID-19. “Happy hypoxia” is an indication that certain patients do not express breathlessness but have impaired oxygenation. It is important to determine the degree of oxygenation an all COVID-19 patients that will predict the severity of the disease and provide an outline of further management plans.Objective: This study aimed to describe the parameters of blood gas analysis in hospitalized patients and analyze its correlation with degree of severity of the diseaseMethods: We conducted observational analysis, cross sectional, single-center study including 71 laboratory-confirmed patients in Dr. Saiful Anwar General Hospital, Malang, Indonesia from April-Juni 2020. Statistical analysis was performed to determine the determine the relation of blood gas analysis with disease severity. Result: Subjects were divided to 25 patients (35,21%) in the mild-moderate group and 46 patients (64,79%) in severe group. Analysis of demographic and clinical characteristic showed that age, history of smoking, dyspnea and oxygen delivery were associated with disease severity (p less than 0,005). Statistical analysis of blood gas analysis showed associated degree of oxygenation with disease severity which is assessed by PaO2, SaO2 BGA, PaO2/FiO2 and original PaO2 (p less than 0,005). Conclusion: In our cross sectional study we found that degree of oxygenation was associated with disease severity in hospitalized COVID-19 patients.